2014
DOI: 10.1242/dev.107938
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/JNK signaling target gene alcam is required for embryonic kidney development

Abstract: Proper development of nephrons is essential for kidney function. β-Catenin-independent Wnt signaling through Fzd8, Inversin, Daam1, RhoA and Myosin is required for nephric tubule morphogenesis. Here, we provide a novel mechanism through which non-canonical Wnt signaling contributes to tubular development. Using Xenopus laevis as a model system, we found that the cell-adhesion molecule Alcam is required for proper nephrogenesis and functions downstream of Fzd3 during embryonic kidney development. We found alcam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…In addition to cytoreductive surgery, cisplatin-based chemotherapy is one of the most important therapeutic strategies for ovarian cancer (2). Previous studies have shown that Wnt signaling pathway deregulation correlates with ovarian cancer cell proliferation, survival, invasion and metastasis (25,26,28,30,31). Furthermore, cisplatin chemoresistance has been an obstacle in the successful treatment of ovarian cancer (8,32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cytoreductive surgery, cisplatin-based chemotherapy is one of the most important therapeutic strategies for ovarian cancer (2). Previous studies have shown that Wnt signaling pathway deregulation correlates with ovarian cancer cell proliferation, survival, invasion and metastasis (25,26,28,30,31). Furthermore, cisplatin chemoresistance has been an obstacle in the successful treatment of ovarian cancer (8,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In the non-canonical Wnt/JNK signaling pathway, Wnt-Fzd binding activates a number of small guanosine-5′-triphosphate (GTP) -binding proteins, including c-Jun N-terminal kinase (JNK), which affect a wide range of cellular processes, including cytoskeleton rearrangement, cell polarity, cell migration and gene expression (28). Previous studies have identified that aberrant Wnt/JNK signaling may initiate and stimulate the development of malignant phenotypes through effects on cell proliferation, survival, polarity, invasion and metastasis (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Besides acting via the non-canonical PCP WNT pathway [29], it can signal through the WNT receptor Fzd3 (reviewed in [30][31][32]). Downstream of WNT receptor Fzd3, the cell adhesion molecule Alcam acts via the non-canonical WNT/JNK pathway to affect proximal tubule development [33]. Strikingly, WNT5A, FZD3 and ALCAM were all upregulated in IRX5 −/− cells (Figure 5B,C).…”
Section: Irx3 and Irx5 Knockout Affects Wnt And Hippo Signalling In Dmentioning
confidence: 97%
“…Among these, we screened ALCAM (P=3.00E-08), HLA-G (P=3.00E-08), and HLA-E (P=3.00E-08), which are closely related to embryonic development, as candidate genes of RM (Cizelsky & Tata 2014;Gelmini et al 2016;Verloes et al 2017).…”
Section: Pathway Enrichment Analysis Of the Dmrsmentioning
confidence: 99%